Migration as a critical humanitarian and development issue in Nigeria: The way forward - Adeyeye, Funke Bukola (Corpus Intellectual, 2024)
Nigeria is blessed with abundant natural, human and material resources; however, corruption, political and economic instability, environmental and other emerging factors continue to impede the Nation’s development thereby leading to forced and irregular migration within and beyond the shores of the Nation. This study relying on secondary sources of qualitative data, aims to understand why migration is a critical humanitarian and development issue in Nigeria, and recommended the capacity strengthening of policy actors, humanitarian and development practitioners as well as introduction of social safety nets and other incentives necessary to buffer the negative effects of factors that influence Migration.